Efforts To Improve Students' Mathematical Concepts Understanding Ability Using Dienes Block Media - Kusnandar, Nandang; Yusuf, Yusfita (Universitas Wiralodra, 2023)
The ability to understand mathematical concepts is one of the most important abilities and must be owned by every student. This happens because the ability to understand concepts is the basis for having other The ability to understand mathematical concepts is one of the most important abilities and must be owned by every student. This happens because the ability to understand concepts is the basis for having other mathematical abilities. However, the reality on the ground, according to the results of observations and interviews with an elementary school (SD) teacher in Sumedang Regency, is known that in learning mathematics, the ability to understand mathematics is still relatively low. One of the media that is expected to improve the ability of students to understand mathematical concepts is dienes block media. This study aims to determine whether there are differences in the ability to understand mathematical concepts between students who receive learning using Dienes block media and students who learn without using Dienes block media in addition material. The method used in this study was quasi-experimental with nonequivalent pre-test-post-test control group design. The instrument used is a test of ability to understand mathematical concepts (pre-test and post-test). The population in this study were all grade II students at SDN Cilengkrang 2022/2023 with a total of 54 people. The sample used was the total sample, namely class II A which consisted of 29 students as the control class and class II B which consisted of 25 students as the experimental class. In the learning process, the experimental class used Dienes block media and the control class did not use Dienes block media. Based on the results of data analysis, it was concluded that there were differences in the ability to understand mathematical concepts between students who received learning using Dienes block media and students who received learning without using Dienes block media in addition material. Students who receive learning with Dienes block media have the ability to understand mathematical concepts better than students who learn without Dienes block media.